Inflammatory bowel disease incidence, prevalence and 12‐month initial disease course in Tasmania, Australia. Issue 5 (13th May 2019) - Bhatia, Rajesh; Yeoh, Sern Wei; Vaz, Karl; Studd, Corrie; Wilson, Jarrad; Bell, Sally; Otahal, Petr; Venn, Alison
Abstract: Background: High inflammatory bowel disease (IBD) rates have been reported in Australasia, but no state‐wide studies have yet been performed. Aim: This study estimates the 1‐year incidence and point prevalence of IBD in the state of Tasmania, Australia. It also reports clinical outcomes after 12 months of diagnosis in an incident cohort. Methods: A prospective, population‐based study was performed collecting prevalent and incident state‐wide cases from 1 June 2013 to 31 May 2014. Case data were identified from specialist doctors, pathology databases and hospital records. Age‐standardised rates (ASR) were calculated based on World Health Organization 2000 standard population characteristics. Incident cases were followed up 12 months after diagnosis. Results: There were 1719 prevalent cases: ASR for IBD, Crohn disease (CD), ulcerative colitis (UC) and inflammatory bowel disease unclassified (IBDU) prevalence rates were 303.9, 165.5, 131.4 and 6.9 per 100 000 respectively. Prevalent CD cases were younger, with greater immunomodulator/biological use and bowel resections. There were 149 incident cases: ASR for IBD, CD, UC and IBDU incidence were 29.5, 15.4, 12.4 and 1.7 per 100 000 respectively. Incident CD cases were more likely than UC or IBDU to require escalation of medical therapy, hospitalisation and bowel resection, especially among those with penetrating or stricturing disease. They had a longer duration of symptoms prior to diagnosis. Conclusion: IBD prevalence and incidence rates are high in Tasmania, comparable to data from other Australasian studies and those from Northern Europe and America. Poorer 12‐month clinical outcomes occurred in complicated CD, with greater use of healthcare resources.